Pengaruh Daya Tarik Iklan, Persepsi Harga dan Kualitas Produk Terhadap Minat Beli E-Commerce Tokopedia (Studi Kasus Generasi Muslim Millenial di Samarinda) - Febri Wulan Sari; Akhmad Nurzaroni; Nurul Fadhilah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
Abstrack This research is motivated by the development of E-Commerce in Indonesia is very high because of the tendency of today's people who want easy, fast and practical so that it triggers the growth of the E-Commerce business. To attract consumer buying interest requires a strategy, namely the attractiveness of advertisements to provide complete information. Perception of price to decide consumers to buy in terms of the price of the product that will be received. Product quality is a deep factor that can indicate whether a product has value or not in a consumer's view. This study aims to determine whether the attractiveness of advertising, price perception and product quality affect the purchase intention of Tokopedia e-commerce in Samarinda. The type of research used in this research is quantitative research with an associative approach. This study uses primary data from a questionnaire or questionnaire. The number of samples in this study were 100 respondents from the millennial Muslim generation with a sampling technique, namely the non-probability sampling technique with the purposive sampling method. The analysis technique used is multiple linear regression test consisting of T test, F test, coefficient of determination with SPSS 21 management tool. The results of this study indicate that partially the advertising attractiveness variable has no significant effect on buying interest, besides the price perception variable (X2) has a significant effect on buying interest (Y), and the product quality variable (X3) has a significant effect on buying interest (Y). Then from the calculation results of the simultaneous test of advertising attractiveness, price perception and product quality have a simultaneous effect on the interest in buying e-commerce Tokopedia in Samarinda. Keywords: Advertising Attractiveness, Price Perception, Product Quality, Purchase Interest.